Evaluation of the acoustic coordinated reset (CR ®) neuromodulation therapy for tinnitus: study protocol for a double-blind randomized placebo-controlled trial - Hoare, Derek J.; Pierzycki, Robert H.; Thomas, Holly; McAlpine, David; Hall, Deborah A. (BioMed Central, 2013)
Background Current theories of tinnitus assume that the phantom sound is generated either through increased spontaneous activity of neurons in the auditory brain, or through pathological temporal firing patterns of the spontaneous neuronal discharge, or a combination of both factors. With this in mind, Tass and colleagues recently tested a number of temporally patterned acoustic stimulation strategies in a proof of concept study. Potential therapeutic sound regimes were derived according to a paradigm assumed to disrupt hypersynchronous neuronal activity, and promote plasticity mechanisms that stabilize a state of asynchronous spontaneous activity. This would correspond to a permanent reduction of tinnitus. The proof of concept study, conducted in Germany, confirmed the safety of the acoustic stimuli for use in tinnitus, and exploratory results indicated modulation of tinnitus-related pathological synchronous activity with potential therapeutic benefit. The most effective stimulation paradigm is now in clinical use as a sound therapy device, the acoustic coordinated reset (CR®) neuromodulation (Adaptive Neuromodulation GmbH (ANM), Köln, Germany).